2021
DOI: 10.1002/anie.202103667
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of 16π Antiaromatic 2,7‐Dihydrodiazapyrenes: Antiaromatic Polycyclic Hydrocarbons with Embedded Nitrogen

Abstract: We describe the two-electron reduction of N,N'dimethyl-2,7-diazapyrenium dications (MDAP 2+ ), which afforded the corresponding reduced form (MDAP 0 ) as a highly electron-rich 16p antiaromatic system. A single-crystal X-ray diffraction analysis of MDAP 0 revealed a distorted quinoidal structure with high bond-length alternation. The 1 H NMR spectrum of MDAP 0 exhibited a diagnostic proton signal (4.6 ppm) that is distinctly upfield shifted compared to that of aromatic diazapyrene (8.3 ppm). Theoretical calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
1
13
0
3
Order By: Relevance
“…In 2021, the same Miyake group comprehensively carried out photophysical studies of 16π antiaromatic 1,3,6,8-tetraaryl- N , N ′-dimethyl-2,7-dihydrodiazapyrene 36b 0 in comparison with N , N ′-dimethyl-2,7-diazapyrenium dication 35b 2+ and 1,3,6,8-tetraaryl- N , N ′-dimethyl-2,7-diazapyrene 24a. 24 The absorption spectrum in THF of 35b 2+ showed a bathochromic shift relative to spectrum 24a and a vibrational structure. However, the longest wavelength maxima of the absorption spectrum in THF (up to 600 nm), as well as a weak and broad absorption band up to 1200 nm, were observed for dihydrodiazapyrene 36b 0 in UV/Vis-NIR region ( Fig.…”
Section: Other Synthetic Approachesmentioning
confidence: 92%
See 3 more Smart Citations
“…In 2021, the same Miyake group comprehensively carried out photophysical studies of 16π antiaromatic 1,3,6,8-tetraaryl- N , N ′-dimethyl-2,7-dihydrodiazapyrene 36b 0 in comparison with N , N ′-dimethyl-2,7-diazapyrenium dication 35b 2+ and 1,3,6,8-tetraaryl- N , N ′-dimethyl-2,7-diazapyrene 24a. 24 The absorption spectrum in THF of 35b 2+ showed a bathochromic shift relative to spectrum 24a and a vibrational structure. However, the longest wavelength maxima of the absorption spectrum in THF (up to 600 nm), as well as a weak and broad absorption band up to 1200 nm, were observed for dihydrodiazapyrene 36b 0 in UV/Vis-NIR region ( Fig.…”
Section: Other Synthetic Approachesmentioning
confidence: 92%
“…And two-electron reduction of the conventional N , N ′-dimethyl-4,4′-bipyridyl dication, methyl viologen (MV 2+ ) did not result in antiaromaticity due to the lack of a cyclic conjugation circuit. In addition, the authors 24 observed a quite low oxidation potential (−1.34 V) for 1,3,6,8-tetraarylated dihydro-2,7-diazapyrene as a result of combination of electron-rich N -heterocyclic system of 2,7-dimetylated dihydro-2,7-diazapyrene and the intrinsic destabilization of the HOMO energy level derived from its 16π antiaromatic nature.…”
Section: Electronic Structure and Homo–lumo-distribution For 27-diaza...mentioning
confidence: 99%
See 2 more Smart Citations
“…Single-crystal X-ray analyses revealed the dicationic nature of MDAP-a 2+ and the quinoidal structure of MDAPa 0 . [19] Single crystals of MDAP-a 2+ were obtained from tetrachloroethane/hexane, while MDAP-a 0 was recrystallized from toluene/acetonitrile under an argon atmosphere. The existence of two triflate counter ions per molecule of MDAPa 2+ in the crystal packing confirmed the dicationic nature of MDAP-a 2+ (Figure 1 b).…”
mentioning
confidence: 99%